2021
DOI: 10.1115/1.4051549
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Experimental Study on Dynamic Characteristics of an Integrated Quasi-Zero Stiffness Isolator

Abstract: The dynamic performance of an integrated quasi-zero stiffness (IQZS) isolator which is constructed by a single elastic structure is investigated in this study. This prototype exhibits the characteristics of the best simplicity, high reliability and without friction by using the minimum number of elements. For completeness, the static properties of the IQZS isolator are provided at first. And then, the dynamic behavior is analyzed and the frequency response under harmonic excitation is derived by using an equiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Zhou et al [48] designed a new type of periodic local resonance metamaterial with QZS characteristics by using a multi segment folded curved beam. Liu et al [49] analyzed the influence of cross-sectional configuration on the dynamic response of an integral quasi-zero isolator. Cai et al [50,51] made the QZS element composed of three folded beams into a metamaterial plate, and explored its low-frequency band gap characteristics for attenuation of bending waves.…”
Section: Introductionmentioning
confidence: 99%
“…Zhou et al [48] designed a new type of periodic local resonance metamaterial with QZS characteristics by using a multi segment folded curved beam. Liu et al [49] analyzed the influence of cross-sectional configuration on the dynamic response of an integral quasi-zero isolator. Cai et al [50,51] made the QZS element composed of three folded beams into a metamaterial plate, and explored its low-frequency band gap characteristics for attenuation of bending waves.…”
Section: Introductionmentioning
confidence: 99%
“…Conventional elastic materials, such as rubber and other polymers, can attenuate high-frequency vibrations well, but require greater thickness for low-frequency vibration attenuation, which unfortunately increases the overall weight of the engineering structures [20,21]. Locally resonant metamaterials possess extensive potential applications in low-frequency vibration and noise reduction [22][23][24], but suffer from limitations, such as the narrow working frequency ranges [25]. On the other hand, mechanism-based vibration isolators, such as quasi-zero stiffness (QZS) isolators, become widely used in broadband low-frequency vibration control [26].…”
Section: Introductionmentioning
confidence: 99%
“…Using annular metal rubber and shape memory alloy actuators, Shen et al [14] developed a resonant frequency-tunable vibration isolator and demonstrated the reliability of the tunable resonant frequency with a resonant frequency identification experiment in a sine sweep test ranging from 5 to 500 Hz. Liu et al [15] designed an integrated quasi-zero stiffness isolator (IQZS) composed of a Symmetry 2022, 14, 2017 2 of 14 single elastic structure and studied its dynamic characteristics through theoretical analysis and experimentation. A dynamic characteristic analysis of inertia-based vibration isolators was conducted, and the vibration performance of the vibration isolators was evaluated through performance criteria [16,17].…”
Section: Introductionmentioning
confidence: 99%